2012
DOI: 10.3109/10717544.2012.657721
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on design of stable etoposide-loaded PEG-PCL micelles: effect of molecular weight of PEG-PCL diblock copolymer on thein vitroandin vivoperformance of micelles

Abstract: (2012) Investigation on design of stable etoposide-loaded PEG-PCL micelles: effect of molecular weight of PEG-PCL diblock copolymer on the invitro and invivo performance of micelles, Drug Delivery, 19:3,[155][156][157][158][159][160][161][162][163][164][165][166][167]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…8 All kinds of macromolecular architectures based on PCL and PEG have been proposed from classical diblock copolymers to triblock copolymers, dendrimer-derived, star or miktoarm architectures. [9][10][11][12][13] The availability of a variety of macromolecular architectures and compositions has proved the potential of these polymer systems for cancer therapy, and the impact of PCL-PEG copolymer amphiphilicity on the formation and shape of self-assemblies, 14,15 drug loading, formulation stability 12,16 and cellular internalization [17][18][19] have been studied. It was also demonstrated that PCL-PEG copolymers could act as modulators of the drug efflux transporter P-glycoprotein in vitro and therefore they could be beneficial for the problematic treatment of multidrug resistant (MDR) cancer tumors.…”
Section: Introductionmentioning
confidence: 99%
“…8 All kinds of macromolecular architectures based on PCL and PEG have been proposed from classical diblock copolymers to triblock copolymers, dendrimer-derived, star or miktoarm architectures. [9][10][11][12][13] The availability of a variety of macromolecular architectures and compositions has proved the potential of these polymer systems for cancer therapy, and the impact of PCL-PEG copolymer amphiphilicity on the formation and shape of self-assemblies, 14,15 drug loading, formulation stability 12,16 and cellular internalization [17][18][19] have been studied. It was also demonstrated that PCL-PEG copolymers could act as modulators of the drug efflux transporter P-glycoprotein in vitro and therefore they could be beneficial for the problematic treatment of multidrug resistant (MDR) cancer tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the CMC value was determined to be 0.35 μg/mL, in the same order of magnitude and much lower than mPEG‐PCL, compared with some other studied polymeric micelles. The lower CMC value, maybe due to the strong the hydrophobic interaction between the hydrophobic segments, enables the use of this novel mixed micelles as drug carriers with the stability to maintain a micelle structure against dissociation and precipitation in blood due to dilution …”
Section: Resultsmentioning
confidence: 99%
“…The lower CMC value, maybe due to the strong the hydrophobic interaction between the hydrophobic segments, enables the use of this novel mixed micelles as drug carriers with the stability to maintain a micelle structure against dissociation and precipitation in blood due to dilution. 28…”
Section: The Tem Of Gna-mmsmentioning
confidence: 99%
“…Micellar complexation may moreover modify the drug disposition in the body by preventing uncontrolled drug distribution and favoring drug accumulation in solid tumors where the discontinuity of the capillaries and the lack of an efficient lymphatic drainage supports the entrapment and retention of nanoparticulate systems such as micelles, liposomes or soluble macromolecules ( 39 , 40 , 47 ). The micellar complexation of Paclitaxel and Etoposide is regarded with great interest to improve their bioavailability ( 48 , 49 ) overcoming the adverse reactions associated with the currently marketed formulations. Indeed, apart from Abraxane®, consisting in nanoparticles of Paclitaxel and human serum albumin, all the other marketed formulations of Paclitaxel and Etoposide contain excipients such as Cremophor-EL, ethanol, benzyl alcohol, polysorbate-80 which have been associated with serious side effects ( 50 ).…”
Section: Discussionmentioning
confidence: 99%